2008
DOI: 10.1186/1471-2431-8-31
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of insulin resistance and its association with metabolic syndrome criteria among Bolivian children and adolescents with obesity

Abstract: Background: Obesity is a one of the most common nutritional disorder worldwide, clearly associated with the metabolic syndrome, condition with implications for the development of many chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
56
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 31 publications
8
56
0
14
Order By: Relevance
“…Assim como nos adultos, a obesidade tem se convertido também em um problema de saúde nas crianças da América Latina, devido ao alto risco de persistência de obesidade na idade adulta e associar-se com o desenvolvimento de hipertensão arterial (22,50,51). 1) Circunferência da cintura aumentada, cuja definição é específica para cada população e para cada país; 2) Triglicerídios iguais ou maiores que 150 mg/dL, ou tratamento farmacológico para triglicerídios séricos elevados; 3) Redução de HDL-colesterol a menos de 40 mg/dL em homens e menos de 50 mg/dL em mulheres.…”
unclassified
“…Assim como nos adultos, a obesidade tem se convertido também em um problema de saúde nas crianças da América Latina, devido ao alto risco de persistência de obesidade na idade adulta e associar-se com o desenvolvimento de hipertensão arterial (22,50,51). 1) Circunferência da cintura aumentada, cuja definição é específica para cada população e para cada país; 2) Triglicerídios iguais ou maiores que 150 mg/dL, ou tratamento farmacológico para triglicerídios séricos elevados; 3) Redução de HDL-colesterol a menos de 40 mg/dL em homens e menos de 50 mg/dL em mulheres.…”
unclassified
“…Finally, a recent study conducted among Bolivian children and adolescents with obesity revealed an IR prevalence of 39?4 % by using a threshold of HOMA-IR . 3?5 (3) . IR in children and adolescents has been associated with CVD and metabolic disorders such as hypertension, dyslipidaemia, hepatic steatosis and endothelial dysfunction (6,7) .…”
mentioning
confidence: 99%
“…The prevalence of insulin resistance (IR) in children and adolescents is increasing around the world (1)(2)(3)(4)(5) . Although there is no universally accepted definition of IR, all studies evaluating the prevalence of IR indicate that more than one out of three obese children or adolescents display IR.…”
mentioning
confidence: 99%
“…The few studies of AN carried out in children or young participants, however, have not considered the knuckles as a site for investigation. 13 , 16 , 18 , 44 They have neither studied the diagnostic performance of AN to predict IR by HOMA-IR index.…”
Section: Discussionmentioning
confidence: 99%